Thymoquinone protects the testes of hypothyroid rats by suppressing pro-inflammatory cytokines and oxidative stress and promoting SIRT1 testicular expression - Algaidi, Sami A.; Faddladdeen, Khadija A.; Alrefaei, Ghadeer I.; Qahl, Safa H.; Albadawi, Emad A.; ALmohaimeed, Hailah M.; Ayuob, Nasra N. (Frontiers in Pharmacology, 2022)
Background: Hypothyroidism was linked with many testicular structural and dysfunctional changes in males. Thymoquinone (TQ) showed a potent testicular protective effect through its antioxidant, anti-inflammatory, anti-apoptotic, fertility-enhancing and endocrine modulatory activities. Objectives: This study aimed to investigate the efficacy of TQ in preserving the testicular structure of a model of experimentally-induced hypothyroidism in rats and identify the mechanism behind this effect. Materials and methods: Propylthiouracil (PTU) was used to induce hypothyroidism in adult male Wistar rats then treated with TQ (50 mg/kg/body weight) for four weeks and compared to the untreated rats. Thyroid hormonal profile, oxidants/antioxidants profile and serum testosterone levels were assessed. Gene and immune-expression of SIRT1 and pro-inflammatory cytokines TNF-α and NF-κB were also assessed in the testicular tissue. Results: TQ administration successfully improved PTU-induced disturbance in thyroid hormonal profile (T3, T4, TSH), serum testosterone level and pancreatic antioxidants compared to the untreated hypothyroid group. TQ significantly downregulated (p=0.001, p˂0.001) TNF-α, NF-κB transcription while, it significantly upregulated (p=0.01) SIRT1 transcription in testes of hypothyroid rats. TQ markedly relieved the histopathological testicular changes induced by PTU and significantly increased (p=0.002, p=0.01) the sectional area of seminiferous tubules and germinal epithelial height, respectively. TUNEL-positive apoptotic germinal cells were significantly decreased (p˂0.001), while PCNA positive proliferating germinal cells and androgen receptor expression were significantly increased (p˂0.001) in testis of TQ-treated hypothyroid rats. Conclusion: Thymoquinone could limit the hypothyroidism-induced structural changes in the testis mostly through the up-regulation of SIRT1 expression which seems to mediate its promising antioxidant, anti-inflammatory and antiapoptotic effects that were evident in this study. Therefore, TQ is recommended as an adjuvant safe supplement in managing hypothyroidism especially in males.